2012
DOI: 10.1111/j.1742-1241.2012.02924.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and the heart

Abstract: Summary Diabetes mellitus is a risk factor for the development of coronary artery disease and chronic heart failure. When carefully screened for, diabetes or prediabetic disorders, are present in the majority of patients with clinically manifest ischaemic heart disease, and confer a major adverse impact upon morbidity and mortality. Important therapeutic modifications are required in the management of coronary artery disease and chronic heart failure associated with diabetes, and vice versa. However, despite o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 107 publications
0
16
0
2
Order By: Relevance
“…This finding was consistent with previous reports. [25][26][27][28][29][30] However, pre-transplant DM was an independent risk factor of NRM in a multivariate analysis that included all other HCT-CI factors. Furthermore, when patients were stratified according to the HCT-CI score that did not include DM, the incidence of NRM in patients with DM was higher than that in those without DM.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was consistent with previous reports. [25][26][27][28][29][30] However, pre-transplant DM was an independent risk factor of NRM in a multivariate analysis that included all other HCT-CI factors. Furthermore, when patients were stratified according to the HCT-CI score that did not include DM, the incidence of NRM in patients with DM was higher than that in those without DM.…”
Section: Discussionmentioning
confidence: 99%
“…However, diabetes impairs not only the liver and kidney but also the heart [19]. Diabetes has a high relevance with cardiovascular diseases including hypertension and ischemic heart disease [20]. Since our previous study showed that OS leaf powder in the diet reduced blood glucose and serum marker enzymes of liver and kidney function in streptozotocin-induced DM rats [9].…”
Section: Introductionmentioning
confidence: 97%
“…Type 2 diabetes mellitus (DM), together with arterial hypertension, obesity, dyslipidemia and smoking, represents one of the most prevalent cardio‐ and cerebrovascular risk factors . At the same time, DM is one of the most important risk factors of cardiac remodeling .…”
mentioning
confidence: 99%